Respuesta :
remember that you can do anything to an equation as long as you do it to both sides
remember the distributive property: a(b+c)=ab+ac
also commutative property of addition: a+b=b+a
so
6(6x-2)+8(1-5x)=2x
distribute
6(6x-2)=6(6x)+6(-2)=36x-12
8(1-5x)=8(1)+8(-5x)=8-40x
36x-12+8-40x=2x
group like terms
36x-40x-12+8=2x
add like terms
-4x-4=2x
add 4x to both sides to get x by itself
4x-4x-4=2x+4x
0-4=6x
-4=6x
divide both sides by 6
-4/6=(6x)/6
-2/3=x(6/6)
-2/3=x(1)
-2/3=x
x=-2/3
the solution is x=-2/3
Answer by JKismyhusbandbae:
[tex]\mathrm{Expand\:}6\left(6x-2\right)+8\left(1-5x\right):\quad -4x-4\\-4x-4=2x\\\mathrm{Add\:}4\mathrm{\:to\:both\:sides}\\-4x-4+4=2x+4\\Simplify\\-4x=2x+4\\\mathrm{Subtract\:}2x\mathrm{\:from\:both\:sides}\\-4x-2x=2x+4-2x\\Simplify\\-6x=4\\\mathrm{Divide\:both\:sides\:by\:}-6\\\frac{-6x}{-6}=\frac{4}{-6}\\Simplify\\x=-\frac{2}{3}[/tex]